Commercialization of oilseeds and pulses stakeholder consultation workshops: Final report - Ahmed, Akhter; Bakhtiar, M. Mehrab; Ghostlaw, Julie; Khan, A. S. M. Mahbubur Rahman; Sultana, Nasreen; Siddique, Rezaul Karim; Kundu, Subrata Kumar; Ahmed, Shamim (International Food Policy Research Institute, 2021)
On September 18, 2020, USAID requested IFPRI to conduct 15 stakeholder consultations on three thematic areas across five districts in the Feed the Future Zone of Influence (ZOI) and Zone of Resilience (ZOR): Barishal, Cox’s Bazar, Dhaka, Jashore, and Khulna. The thematic areas are: (1) Increased Access to Finance, (2) Commercialization of Oilseeds and Pulses, and (3) Commercialization of Agricultural Research and Biotechnology. IFPRI agreed to conduct these stakeholder consultations and, on October 21, 2020, USAID approved IFPRI’s Commercialization of Oilseeds and Pulses concept note.